Production and partial characterization of serine and metallo peptidases secreted by Aspergillus fumigatus Fresenius in submerged and solid state fermentation - Silva, Ronivaldo Rodrigues da [UNESP]; Cabral, Tatiana Pereira de Freitas; Rodrigues, André [UNESP]; Hamilton, Cabral (Sociedade Brasileira de Microbiologia, 2013)
Enzyme production varies in different fermentation systems. Enzyme expression in different fermentation systems yields important information for improving our understanding of enzymatic production induction. Comparative studies between solid-state fermentation (SSF) using agro-industrial waste wheat bran and submerged fermentation (SmF) using synthetic media were carried out to determinate the best parameters for peptidase production by the fungus Aspergillus fumigatus Fresen. Variables tested include: the concentration of carbon and protein nitrogen sources, the size of the inoculum, the pH of the media, temperature, and the length of the fermentation process. The best peptidase production during SSF was obtained after 96 hours using wheat bran at 30 ºC with an inoculum of 1 x 10(6) spores and yielded 1500 active units (UµmL). The best peptidase production using SmF was obtained after periods of 72 and 96 hours of fermentation in media containing 0.5% and 0.25% of casein, respectively, at a pH of 6.0 and at 30 ºC and yielded 40 UµmL. We also found examples of catabolite repression of peptidase production under SmF conditions. Biochemical characterization of the peptidases produced by both fermentative processes showed optimum activity at pH 8.0 and 50 ºC, and also showed that their proteolytic activity is modulated by surfactants. The enzymatic inhibition profile using phenylmethylsulfonyl fluoride (PMSF) in SmF and SSF indicated that both fermentative processes produced a serine peptidase. Additionally, the inhibitory effect of the ethylene-diaminetetraacetic acid (EDTA) chelating agent on the peptidase produced by SmF indicated that this fermentative process also produced a metallopeptidase.
Keywords: metallopeptidase; serine peptidase; fermentative parameters; Aspergillus fumigatus